Psychological characteristics of professional activities athletes and their rolein the socialization process - Sidorova, A. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
The article contains some features of professional socialization of athletes, and the role of mass sports in the process of socialization in the modern society. Motivation of achievment is shown as the most important factor in socialization and self identity of athlete.